Hubungan Antara Dukungan Sosial Teman Sebaya dengan Stres Akademik Pembelajaran Daring pada Masa Pandemi Covid-19 - Nopriadi; A An Defitri Basar; Ririn Muthia Zukhra (HEALTH CARE : JURNAL KESEHATAN, 2021)
Online learning causes academic stress. Academic stress occurs due to not achieving adjustments and failure to face academic demands. Unresolved academic stress can affect thoughts, feelings, physical and behavior. Academic stress can be reduced by the presence of peer social support. This study was aimed to examine the relationship between peer social support and the academic stress of online learning. This study was aimed to examine the relationship between peer social support and the academic stress of online learning. The study used Correlation descriptive design with cross sectional approach. The study was conducted at the Faculty of Nursing, University of Riau with a sample of 213 respondents by using proportionate stratified random sampling. The measuring instrument used is a questionnaire of academic stress and social support modified by the researcher with a validity range of 0.458-0.802 and 0.461-0.574. The analysis used univariate analysis and bivariate analysis. The results showed that majority of respondents were female, namely 200 (93.3%), aged 20 years were 77 (36.2%) and from batch A 2020 is 75 (35.2%). The Majority of respondents who received high peer social support experienced heavy online learning academic stress levels as much as 35 (28.7%) and moderate academic stress as many as 87 (71.3%). Statistical test results obtained p value = 0.020 < (0.05) meaning Ho is rejected The conclusion of the study is that There was a relationship between peer social support and academic stress of online learning during the COVID-19 pandemic.